Travelling fire experiments in steel-framed structure: numerical investigations with CFD and FEM. (21st May 2021) - Charlier, Marion; Glorieux, Antoine; Dai, Xu; Alam, Naveed; Welch, Stephen; Anderson, Johan; Vassart, Olivier; Nadjai, Ali
Abstract : Purpose: The purpose of this paper is to propose a simplified representation of the fire load in computational fluid dynamics (CFD) to represent the effect of large-scale travelling fire and to highlight the relevance of such an approach whilst coupling the CFD results with finite element method (FEM) to evaluate related steel temperatures, comparing the numerical outcomes with experimental measurements. Design/methodology/approach: This paper presents the setup of the CFD simulations (FDS software), its corresponding assumptions and the calibration via two natural fire tests whilst focusing on gas temperatures and on steel temperatures measured on a central column. For the latter, two methods are presented: one based on EN 1993-1-2 and another linking CFD and FEM (SAFIR ® software). Findings: This paper suggests that such an approach can allow for an acceptable representation of the travelling fire both in terms of fire spread and steel temperatures. The inevitable limitations inherent to the simplifications made during the CFD simulations are also discussed. Regarding steel temperatures, the two methods lead to quite similar results, but with the ones obtained via CFD–FEM coupling are closer to those measured. Originality/value: This work has revealed that the proposed simplified representation of the fire load appears to be appropriate to evaluate the temperature of steel structural elements within reasonable limits on computational time, making it potentially desirable for practical applications. This paper also presents the first comparisons of FDS–SAFIR ® coupling with experimental results, highlighting promising outcomes.